Screening for Natural Inhibitors of Topoisomerases I from Rhamnus davurica by Affinity Ultrafiltration and High-Performance Liquid Chromatography–Mass Spectrometry - Chen, Guilin; Guo, Mingquan (Frontiers in Plant Science, 2017)
Topoisomerase I (Topo I) catalyzes topological interconversion of duplex DNA during DNA replication and transcription, and has been deemed as important antineoplastic targets. In this study, the fraction R.d-60 from ethyl acetate extracts of Rhamnus davurica showed higher inhibitory rates against SGC-7901 and HT-29 compared with the R.d-30 fraction in vitro. However, the specific active components of R.d-60 fraction remain elusive. To this end, a method based on bio-affinity ultrafiltration and high performance liquid chromatography/electrospray mass spectrometry (HPLC- ESI-MS/MS) was developed to rapidly screen and identify the Topo I inhibitors in this fraction. The enrichment factors (EFs) were calculated to evaluate the binding affinities between the bioactive constituents and Topo I. As a result, eight ligands were identified and six of which with higher EFs showed more potential antitumor activity. Furthermore, antiproliferative assays in vitro (IC50 values) with two representative candidates (apigenin, quercetin) against SGC-7901, HT-29 and Hep G2 cells were conducted and further validated. Finally, the structure-activity relationships revealed that flavones contain a C2-C3 double bond of C ring exhibited higher bio-affinities to Topo I than those without it. This integrated method combining Topo I ultrafiltration with HPLC-MS/MS proved to be very efficient in rapid screening and identification of potential Topo I inhibitors from the complex extracts of medicinal plants, and could be further explored as a valuable high-throughput screening platform in the early drug discovery stage.